An incentivized HIV counseling and testing program targeting hard-to-reach unemployed men in Cape Town, South Africa - Nglazi, Mweete D. (2012)
BACKGROUND: In Southern Africa, men access HIV counseling and testing (HCT) services less than women. Innovative strategies are needed to increase uptake of testing among men. This study assessed the effectiveness of incentivized mobile HCT in reaching unemployed men in Cape Town, South Africa. METHODS: A retrospective analysis of HCT data collected between August 2008 and August 2010 from adult men accessing clinic-based stationary and non-incentivized and incentivized mobile services. Data from these three services were analyzed using descriptive statistics and log-binomial regression models. RESULTS: A total of 9416 first time testers were included in the analysis: 708 were clinic-based, 4985 were non-incentivized and 3723 incentivized mobile service testers. A higher HIV prevalence was observed among men accessing incentivized mobile testing 16.6% (617/3723) compared to those attending non-incentivized mobile 5.5% (277/4985)] and clinic-based services 10.2% (72/708)]. Among men testing at the mobile service, greater proportions of men receiving incentives were self-reported first-time testers (60.1% vs. 42.0%) and had advanced disease (14.9% vs. 7.5%) compared to men testing at non-incentivized mobile services. Furthermore, compared to the non-incentivized mobile service, the incentivized service was associated with a 3-fold greater yield of newly diagnosed HIV infections. This strong association persisted in analyses adjusted for age and first-time versus repeat testing (RR 2.33 95% CI 2.03–2.57]; p<0.001). CONCLUSIONS: These findings suggest that incentivized mobile testing services may reach more previously untested men and significantly increase detection of HIV infection in men.